Answer:
![\mu_k=0.27](https://img.qammunity.org/2021/formulas/physics/college/2pgafki4iwt84qvsospcl6dw7nqlck2v19.png)
Step-by-step explanation:
According to the free body diagram, in this case, we have:
![\sum F_x:-F_k=ma\\\sum F_y:N=mg](https://img.qammunity.org/2021/formulas/physics/college/qp0qo78htlt2t7jm7f4rv9sxr4jtwu51re.png)
Recall that the force of friction is given by:
![F_k=\mu_k N](https://img.qammunity.org/2021/formulas/physics/college/lz7mtnxo7ytoi0m6tmutgvplracx8mcwx2.png)
Replacing and solving for the coefficient of kinetic friction:
![-\mu_kN=ma\\-\mu_k(mg)=ma\\\mu_k=-(a)/(g)](https://img.qammunity.org/2021/formulas/physics/college/bdtviqe1fe1zbe41fste7ixvj0qjsy19ld.png)
We have an uniformly accelerated motion. Thus, the acceleration is defined as:
![a=(v_f-v_0)/(t)\\a=(0-5(m)/(s))/(1.9s)\\a=-2.63(m)/(s^2)](https://img.qammunity.org/2021/formulas/physics/college/o4xtkvu1yz3cosybqvq1qjcgn6snzipj1j.png)
Finally, we calculate
:
![\mu_k=-(-2.63(m)/(s^2))/(9.8(m)/(s^2))\\\mu_k=0.27](https://img.qammunity.org/2021/formulas/physics/college/3irtywwb5bfxpw48btpglcqhpfc8r9l3pb.png)